Roadside assessment of a modern city bus fleet: Gaseous and particle emissions. (July 2019) - Liu, Qianyun; Hallquist, Åsa M.; Fallgren, Henrik; Jerksjö, Martin; Jutterström, Sara; Salberg, Håkan; Hallquist, Mattias; Le Breton, Michael; Pei, Xiangyu; Pathak, Ravi Kant; Liu, Tengyu; Lee, Berto; et al.
Abstract: In many cities worldwide, modern fleets have been introduced to reduce gaseous and particle emissions from city buses. To date, most emission studies are limited to a few vehicles, making a statistically significant assessment of control options difficult, especially under real-world driving conditions. Exhaust emissions of 234 individual city buses were measured under real-world stop-and-go traffic conditions at a bus stop in Gothenburg, Sweden. The buses comprised models fulfilling Euro III-VI and EEV (Enhanced Environmentally Friendly Vehicle) standards with different engine technologies, fuels, and exhaust after-treatment systems, and also included hybrid-electric buses (HEV). Both gaseous (NOx, CO, HC, and SO2 ) and size-resolved particle number (PN) and mass (PM) emission factors (EF) were calculated for vehicles using compressed natural gas (CNG), diesel (DSL), Rapeseed Methyl Ester (RME) and Hydro-treated Vegetable Oil (HVO) equipped with various after-treatment technologies, e.g., diesel particulate filter (DPF), selective catalytic reduction (SCR) and exhaust gas recirculation (EGR) systems. The highest median EFPN was obtained from Euro VHEV -HVO-SCR buses ( Md EFPN = 18×10 14 # kg -1 ) when their combustion engines were used though 53% of their accelerations were below detection limits indicating the use of their electrical engine. The highest Md EFPM was obtained from the Euro V-DSL-SCR buses ( Md EFPM = 150 mg kg -1 ) and the lowest from EEV-CNG buses (below detection threshold) and Euro VIHEV -HVO- SCR+EGR+DPF buses ( Md EFPM = 19 mg kg -1 ). The highest Md EFNOx was obtained from the Euro V-RME-SCR ( Md EFNOx = 30 g kg -1 ) and Euro VHEV -HVO-SCR buses ( Md EFNOx = 24 g kg -1 ), and the lowest from CNG buses ( Md EFNOx = 4.8 g kg -1 ) and Euro VIHEV -HVO-SCR+EGR+DPF buses ( Md EFNOx = 7.4 g kg -1 ). Hybrid buses can give higher PN emissions compared to traditional diesel engines, likely due to downsized combustion engines. Replacing diesel by biodiesel fuel reduced Md EFPM significantly but increased Md EFNOx which may be due to the higher combustion temperature and oxygen contents of the fuel (for RME). Overall, the EEV-CNG buses performed the best regarding both the Md EF and low contribution to the high emitters. It was also found that a small (5%) proportion of the buses contributed significantly (14-30%) to the total emissions. Identification and monitoring the maintenance of the high emitters in the fleets should be considered for the improvement of air quality. Graphical abstract: Image 1 Highlights: Hybrid buses can give higher PN emissions compared to traditional diesel engines. Replacing diesel by biodiesel fuel reduced PM EFs significantly but can increase NOx EFs. A small proportion of the buses contributed significantly to the total emissions.